Spin-3/2 Ising model on a two-layer Bethe lattice with FM/AFM interactions - Albayrak, E.; Yigit, A. (Condensed Matter Physics, 2009)
Two-layer Bethe lattice whose lattice sites are occupied with spin-3/2 atoms is solved exactly by using the recursion relations in a pairwise approach for given coordination numbers q = 3, 4 and 6 with equal external magnetic fields acting on the layers. The ferromagnetic (FM) and antiferromagnetic (AFM) interactions for the spins of the upper and lower layers, respectively, and either FM or AFM type interactions between the adjacent spins of the layers are assumed. The phase diagrams of the model are studied on different planes for given system parameters by obtaining the ground state (GS) phase diagrams and the thermal variations of the order parameters and the response functions, i. e. the susceptibility and the specific heat, in detail. It was found that the model presents both second- and first-order phase transitions. The reentrant behavior is seen when the model presents two N´eel temperatures for higher q values. The existence of the tricritical point and critical end points is also confirmed.